PROMOTING ONLINE TEACHING ABILITIES OF COMPUTER TEACHER STUDENTS THROUGH REMOTE LEARNING ACTIVITIES WITH COMPETENCY-SIMULATED CLASSROOM - Sinlapaninman, Unyaparn (International Online Journal of Education and Teaching, 2022)
This study aimed to 1) investigate the results of remote learning combined with competency-based classroom simulation activities, including academic achievement, the ability to teach online, and learning satisfaction, and 2) compare among the self-assessment, the lecturer’s assessment, and the classmates’ assessment of the pre-service computer teachers’ online teaching ability. The samples consisted of 18 fourth-year students who were chosen by using a cluster random sampling lottery method. A unit is a group of classes. The statistics employed in the research were mean, standard deviation, t-test (Dependent Samples), and F-test (One-way ANOVA). The findings were reported that students had post-test scores higher than pre-test scores at the level of 0.05. The self-assessment, lecturer’s assessment, and the classmates’ assessment of the pre-service computer teachers’ online teaching ability were at the highest level. The students' satisfaction with remote learning combined with competency-based classroom simulation activities taught online by pre-service computer teachers was at the highest level, and in the overall aspect, the comparative results of the pre-service computer teachers’ self-assessment, the lecturer’s assessment, and the classmates’ assessment were not different.